2022
DOI: 10.1101/2022.01.18.22269300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Capturing intrahost recombination of SARS-CoV-2 during superinfection with Alpha and Epsilon variants in New York City

Abstract: Recombination is an evolutionary process by which many pathogens generate diversity and acquire novel functions. Although a common occurrence during coronavirus replication, recombination can only be detected when two genetically distinct viruses contemporaneously infect the same host. Here, we identify an instance of SARS-CoV-2 superinfection, whereby an individual was simultaneously infected with two distinct viral variants: Alpha (B.1.1.7) and Epsilon (B.1.429). This superinfection was first noted when an A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…This process may similarly occur during accelerated SARS-CoV-2 evolution in chronically infected persons. While intrahost recombination may accelerate intrahost divergence (Jackson et al, 2021;Wertheim et al), we did not find evidence for recombination leading to the distinct genotypes found during this chronic infection. This might be an indication for the separated spatial distribution of the viral populations as recombination events would be expected if different genotypes were to be found in the same tissues and cells.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…This process may similarly occur during accelerated SARS-CoV-2 evolution in chronically infected persons. While intrahost recombination may accelerate intrahost divergence (Jackson et al, 2021;Wertheim et al), we did not find evidence for recombination leading to the distinct genotypes found during this chronic infection. This might be an indication for the separated spatial distribution of the viral populations as recombination events would be expected if different genotypes were to be found in the same tissues and cells.…”
Section: Discussioncontrasting
confidence: 83%
“…The long duration of this infection, which spanned the emergence of multiple variants (e.g., Alpha, Delta, Omicron), provided favorable conditions for recombination. The occurrence of recombination in the SARS-CoV-2 genome has been demonstrated (Jackson et al, 2021;Wertheim et al). Therefore, we hypothesized that recombination may have occurred during the chronic infection between coexisting B.1.517 genotypes and between B.1.517 genotypes and other circulating variants transiently causing undetected co-infections.…”
Section: No Evidence For Intrahost Recombination During Chronic Infec...mentioning
confidence: 99%
“…In addition, it was deemed that up to 5% of SARS-CoV-2 that circulated in the USA and UK might have been recombinants (VanInsberghe et al, 2021), and estimated that ≈2.7% of sequenced SARS-CoV-2 genomes might have recombinant ancestry (Turkahia et al, 2021). As a matter of fact, cases of detection of recombinant genomes are increasingly reported in 2022 (Wertheim et al, 2022; Sekizuka et al, 2022; Colson et al, 2022b; Lacek et al, 2022; Bolze et al, 2022; Ou et al, 2022; Belen Pisano et al, 2022; Burel et al, 2022). Such recombinants are all the more likely to be generated when different variants co-circulate with high incidence levels.…”
Section: Discussionmentioning
confidence: 99%
“…Such genetic recombinations are extremely frequent for viruses of family Coronaviridae , and they have already been identified for endemic human coronaviruses (Lai, 1996; Zhang et al, 2015; So et al, 2019; Gribble et al, 2020). Regarding SARS-CoV-2, the occurrence of recombinations has been reported or suspected (Yi, 2019; Yeh and Contreras, 2020; Haddad et al, 2021; Ignatieva et al, 2021; Jackson et al, 2021; Taghizadeh et al, 2021; Varabyou et al, 2021; Kreier, 2022; Wertheim et al, 2022; He et al, 2022; Sekizuka et al, 2022; Colson et al, 2022b; Lacek et al, 2022; Lohrasbi-Nejad, 2022; Bolze et al, 2022; Ou et al, 2022; Belen Pisano et al, 2022; Burel et al, 2022). Very recently, we described the identification and culture of two SARS-CoV-2 recombinants, one between the B.1.160 and Alpha/20I variants in a patient chronically-infected with SARS-CoV-2 (Burel et al, 2022), and another between the Delta/21J AY.4 and Omicron 21K/BA.1 variants in patients infected approximately 10 weeks after the start of the period of co-detection of these two variants in our geographical area (Colson et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Such genetic recombinations are extremely frequent for viruses of family Coronaviridae , and they have already been identified for endemic human coronaviruses ( Lai, 1996 ; Zhang et al, 2015 ; So et al, 2019 ; Gribble et al, 2021 ). Regarding SARS-CoV-2, the occurrence of recombinations has been reported or suspected ( Yi, 2020 ; Yeh and Contreras, 2020 ; Haddad et al, 2021 ; Ignatieva et al, 2022 ; Jackson et al, 2021 ; Taghizadeh et al, 2021 ; Varabyou et al, 2021 ; Kreier, 2022 ; Wertheim et al, 2022 ; He et al, 2022 ; Sekizuka et al, 2022 ; Colson et al, 2022b ; Lacek et al, 2022 ; Lohrasbi-Nejad, 2022 ; Bolze et al, 2022 ; Ou et al, 2022 ; Belén Pisano et al, 2022 ; Burel et al, 2022 ). Very recently, we described the identification and culture of two SARS-CoV-2 recombinants, one between the B.1.160 and Alpha/20I variants in a patient chronically-infected with SARS-CoV-2 ( Burel et al, 2022 ), and another between the Delta/21J AY.4 and Omicron 21K/BA.1 variants in patients infected approximately 10 weeks after the start of the period of co-detection of these two variants in our geographical area ( Colson et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%